Factors Influencing Health-promoting Behaviors in Preventing Coronavirus Disease 2019 Among the Elderly in Kut TUM Subdistrict, Mueang District, Chaiyaphum Province: Factors Influencing Health-promoting Behaviors in Preventing Coronavirus Disease 2019 Among the Elderly in Kut TUM Subdistrict, Mueang District, Chaiyaphum Province - Phakphum, Kittiwin; Kangkarn, Pitukpong (RATANABUTH JOURNAL, 2026)
This research aimed to: 1) examine the level of health-promoting behaviors for COVID-19 prevention among the elderly; 2) investigate factors influencing health-promoting behaviors; 3) explore the relationships between perceived benefits, perceived barriers, and perceived self-efficacy and health-promoting behaviors among the elderly; and 4) propose guidelines for developing health behavior promotion among the elderly in the study area. This research employed a mixed-methods design, incorporating both quantitative and qualitative approaches. Data collection instruments consisted of a questionnaire and in-depth interview guide, with a Cronbach’s alpha reliability coefficient of 0.937. The quantitative sample comprised 381 elderly individuals in Kut Tum Sub-district, Mueang District, Chaiyaphum Province, calculated from a population of 5,589 using Taro Yamane’s formula at a 0.05 margin of error. Ten key informants participated in the qualitative phase. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, and multiple regression analysis, while qualitative data were analyzed through content analysis. The findings revealed that: 1) the overall level of health-promoting behaviors for COVID-19 prevention among the elderly was at a moderate level, with perceived self-efficacy recording the highest mean score, followed by perceived benefits and perceived barriers, respectively; 2) factors related to health responsibility, physical exercise, spiritual development, and stress management significantly influenced health-promoting behaviors among the elderly; and 3) support from family, community, and local health networks played a significant role in promoting health behaviors among the elderly.